2020
DOI: 10.1002/mpr.1818
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing schizophrenia with network analysis and a machine learning method

Abstract: Objective Schizophrenia is a chronic and debilitating neuropsychiatric disorder. It has been suggested that impaired brain connectivity underlies the pathophysiology of schizophrenia. Network analysis has thus recently emerged in the field of schizophrenia research. Methods We investigated 48 schizophrenia patients and 24 healthy controls using network analysis and a machine learning method. A number of global and nodal network properties were estimated from graphs that were reconstructed using probabilistic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 98 publications
(138 reference statements)
0
40
0
1
Order By: Relevance
“…Based on the summary table provided in Table 5, there are 6 articles that applied various machine learning approaches to identify and predict the schizophrenia patients with different data sets [20][21][22][23][24][25]. Several research projects have been conducted to analyze and classify depression and anxiety.…”
Section: Critical Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the summary table provided in Table 5, there are 6 articles that applied various machine learning approaches to identify and predict the schizophrenia patients with different data sets [20][21][22][23][24][25]. Several research projects have been conducted to analyze and classify depression and anxiety.…”
Section: Critical Analysis and Discussionmentioning
confidence: 99%
“…In terms of sample data sets used by the researchers, the data sets used for the classification are mostly small size, which is below 100 subjects. For example, the authors Jo et al [21], Yang et al [22], Rocha-Rego et al [34], Grotegerd et al [35], Mouraō-Miranda et al [37], Akinci et al [39], Wu et al [40], Vergyri et al [46], Salminen et al [47], and Rangaprakash et al [48] have applied small size of sample data for the classifications. Moreover, some studies are conducted by using a partial large size of the data set, which is above 100 subjects.…”
Section: Critical Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining cortical thickness, gyrification of gray matter, and fractional anisotropy and mean diffusivity of white matter, Liang et al (2019) used a gradient boosting decision tree to identify SCZ patients, reaching an average accuracy of 76.54%. Using global and nodal network properties derived from a graph theory analysis, Jo et al (2020) revealed that functional network properties had a high discriminatory ability for classifying SCZ patients and HCs. Using betweenness centrality from graph theoretical approaches and a SVM algorithm, Cheng et al (2015) found a classification accuracy of around 80% for differentiating SCZ patients from non-psychiatric HCs.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of ML models, Jo et al [117] used network analysis and ML methods to classify SCZ and HC. Bae et al [118] used an SVM model, and nine features were selected as input.…”
Section: Schizophreniamentioning
confidence: 99%